GAMBARAN PENGGUNAAN ANTIHIPERTENSI DI PUSKESMAS OGAN PERMATA INDAH - Ainun Wulandari; Teodhora Narendra; Sonia Mutiara (Jurnal Endurance, 2023)
Hypertension is a condition that increases blood pressure to more than 140 mmHg and diastolic blood pressure to more than 90 mmHg. The purpose of this study was to know the description of using hypertension drugs for outpatient in Ogan Permata Indah Health Center. This research is a non-experimental descriptive method and retrospective data collection. The data is taken from the medical patients’ Permata Indah Health Center records. The results of the study used 86 samples, it was found that most patients in this study were female (54,48%), with the age range of 60-74 years (65,11%), with the highest stage II hypertension (65,11%), and the most comorbidities, namely diabetes mellitus (29,07%). The most antihypertensive drug class was CCB, with the most drug being amlodipine (96,51%). The therapy pattern at most was monotherapy with the most drug, namely amlodipine (96,51%), and the use of polytherapy with 2 drugs with the highest combination of CCB and ACEI (3,49%). The suitability of the selection of appropriate antihypertensive drugs for all patients was said to be appropriate (100%), and the suitability of dose selection of antihypertensive drugs with of the appropriate dose category as much as patients (100%).